Análise de uma expeirência de aprendizagem utilizando o Orkut no Instituto Federal Sul-Riograndense - Campus Passo Fundo - Lokchin, Ricardo Santos (2010)
Historically, students present difficulties in understanding the logic of thought, which is necessary to the subject called Logic and Language of Programming. Such difficulty requires a greater effort in studying outside school. Having in mind that learning envelops communicative and collective processes, we believe that opening spaces of interaction among students in a varied schedule, can, somehow, act on the presented difficulty. Acknowledging that students use those digital communication environments, such as social media, this research aims at verifying which developments of a teaching strategy based on Orkut are. It also aims at how they will qualify the learning process in the subject. This research was carried out with 24 students of the Instituto Federal Sul-Rio-Grandense Campus Passo Fundo. Fieldwork was conducted from 06/14/2010 to 07/11/2010. To perform the learning experience mediated by the social media, we used as our foundation the Ten Learning Commandments by Juan Ignacio Pozo, in which teachers could base their interventions. The research took the form of literature and case study. With experience we found that Orkut can be used as a support tool in the discipline not only in a short space of time, and without the requirement of the student and teacher access the environment at all times